Factors behind loyalty in banking - a study based on state-owned commercial banks in Bangladesh - Islam, Serajul; Shahabuddin, AM; Chowdhury, Najneen Jahan (IIUC Studies, 2018)
This paper focuses on the causes of customer satisfaction and its relationship with loyalty in state-owned banking in Bangladesh. The study was conducted in ten branches of six state-owned commercial banks in Chittagong metropolitan area of Bangladesh. Some of the most influencing factors of loyalty have been identified in the study such as having understanding the specific needs of their customers; providing services timely, caring to customers, having required knowledge and skill of employees to perform the services and so on. This study provides some guidelines for developing customer loyalty in banking services. IIUC Studies Vol.13 December 2016: 27-42